Efek pemberian pakan berlebih berupa limbah sayuran pakcoy terhadap daya cerna, tingkat penurunan limbah, dan kandungan protein pada lalat tentara hitam (Hermetia illucens (Linnaeus)) - Agus Dana Permana; Ramadhani Eka Putra; Raeka Okata Soebakti; Ida Kinasih (Jurnal Entomologi Indonesia, 2021)
One of the recent organic waste management programs actively developed is organic waste bioconversion by using larvae of black soldier fly (Hermetia illucens (Linnaeus)). However, one major challenge in organic waste management in Indonesia is the limited space to manage the wastes at waste collection centers. This condition increases the number of wastes to be converted (consumed) by larvae of soldier fly. In this study, the condition was imitated in the laboratory where larvae were individually fed with a large number of wastes. Larvae were divided into 4 groups and were fed with 200, 300, 400, and 500 mg/larva/day of rotten vegetable waste (Pakcoy) and were replicated 3 times. Variables observed during the study were the growth rate, consumption capability, level of waste reduction (waste reduction index, WRI), consumption efficiency (efficiency of conversion of digested-feed, ECD), the weight of harvested biomass, and protein content of larvae, pupae, and adults. The results showed that there was no significant correlation between the weight of harvested biomass and the amount of substrate provided to larvae (one-way ANOVA, P > 0.05). The increasing amount of substrate reduced the efficiency of waste reduction and consumption (one-way ANOVA, P < 0.05). This study also showed that the possible upper limit of consumption capability of larvae was 400 mg/larva/day. On the other hand, the increasing amount of substrate increased the protein content of biomass of each developmental stage.